2022
DOI: 10.3390/agriculture12040441
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mechanization and Investments on the Technical Efficiency of Cassava Farms in Cambodia

Abstract: Cassava is one of the most important cash crops in Cambodia. Agricultural mechanization promotes productivity, but overinvestment may disrupt the balance between inputs and outputs. Depending on the production scale, sometimes hiring equipment is considered better than purchasing it. While we can hypothesize that mechanization and investments might be crucial factors of productivity, technical efficiency analysis for estimating their effects has not yet been conducted. Therefore, this study investigates the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Moreover, there are several constraints that can impact cassava production profitability, including the rise in labor costs and the prices of agricultural inputs and services due to high inflation (Hing & Thun, 2009). Baba et al (2022) conducted a study using the Cobb-Douglas stochastic frontier production model in the Battambang and Pailin provinces, and revealed a significant positive effect of tractor or truck hire costs on cassava "yield"; the cost of cassava uprooting machines had a negative and significant impact. These aspects of input costs may also have implications for cassava profitability.…”
Section: Field Observation and Literature Reviewmentioning
confidence: 99%
“…Moreover, there are several constraints that can impact cassava production profitability, including the rise in labor costs and the prices of agricultural inputs and services due to high inflation (Hing & Thun, 2009). Baba et al (2022) conducted a study using the Cobb-Douglas stochastic frontier production model in the Battambang and Pailin provinces, and revealed a significant positive effect of tractor or truck hire costs on cassava "yield"; the cost of cassava uprooting machines had a negative and significant impact. These aspects of input costs may also have implications for cassava profitability.…”
Section: Field Observation and Literature Reviewmentioning
confidence: 99%
“…The invention of the iron plough and the ridge cultivation technique and the introduction of drought-tolerant plants were landmark events in the history of Chinese agricultural technology. To improve agricultural power, the straight shaft plough, curved shaft plough and mechanized farming tools were invented in the Warring States in the Tang Dynasty (618-907 AD) and after the founding of the People's Republic of China (PRC) in 1949 [3,9,41]. The ridge cultivation technique is an important drought-resistant technology that began in Western Zhou (1046-771 BC), was developed in the Warring States and matured in the Ming and Qing Dynasties (1368-1911 AD) [42].…”
Section: Climate Agricultural Technique Grain Yield Per Unit Area And...mentioning
confidence: 99%
“…To investigate how local fruit growers are adapting and mitigating the effects of climate change, a thorough analysis is needed. Studies have shown that the agricultural sector in various regions, including Tuban City in Indonesia [9], Tanzania [10], Nepal [11], and Samar in the Philippines [12], have explored alternative crops, conservation of genetic resources, and farming strategies to improve sustainability, resilience, and profitability. These studies provide valuable insights into the potential of underutilized crops, the importance of genetic diversity, and the impact of farming practices on profit optimization.…”
Section: Introductionmentioning
confidence: 99%